Нормативно-правове забезпечення систем захисту інформації - Книш, А. О. (ХНУРЕ, 2023)
This work will consider the most basic laws of the legislative framework of Ukraine on information protection, state institutions that ensure control over the proper use of information, its storage and processing, as well as compliance with legislation, personal data protection and the development of information technologies in Ukraine, shortcomings of Ukrainian regulatory and legal support of information protection systems and proposals for correction.